S‐Nitrosylation of Bcl‐2 Negatively Affects Autophagy in Lung Epithelial Cells. Issue 2 (February 2016) - Wright, Clayton; Iyer, Anand Krishnan V.; Kulkarni, Yogesh; Azad, Neelam
ABSTRACT: Autophagy is a catabolic cellular mechanism involving lysosomal degradation of unwanted cellular components. Interaction between Beclin‐1 and Bcl‐2 proteins is known to play a critical role in the initiation of autophagy. We report that malignantly transformed lung epithelial cells are resistant to autophagy and express lower basal levels of autophagic proteins, Beclin‐1 and LC3‐II as compared to non‐tumorigenic cells. Additionally, increased levels of nitric oxide (NO) and Bcl‐2 were observed in transformed cells. Nitric oxide was found to negatively regulate autophagy initiation and autophagic flux by nitrosylating Bcl‐2 and stabilizing its interaction with Beclin‐1, resulting in inhibition of Beclin‐1 activity. An increase in the apoptotic initiator caspase‐9 and the apoptosis and autophagy‐associated kinase p38/MAPK in both cell types indicated possible autophagy–apoptosis crosstalk. Pre‐treatments with ABT‐737 (Bcl‐2 inhibitor) and aminoguanidine (NO inhibitor), and transfection with a non‐nitrosylable Bcl‐2 cysteine double‐mutant plasmid resulted in increased autophagic flux (LC3‐II/p62 upregulation) corresponding with decreased S ‐nitrocysteine expression, thus corroborating the regulatory role of Bcl‐2 S ‐nitrosylation in autophagy. In conclusion, our study reveals a novel mechanism of autophagy resistance via post‐translational modification of Bcl‐2 protein by NO, which may be critical in driving cellular tumorigenesis. J. Cell. Biochem. 117: 521–532, 2016. © 2015 Wiley Periodicals, Inc.